Genetic characterization of Plasmodium vivax isolates from Pakistan using circumsporozoite protein (pvcsp) and merozoite surface protein-1 (pvmsp-1) genes as genetic markers - Zainab Bibi; Anam Fatima; Rehana Rani; Ayesha Maqbool; Samea Khan; Shumaila Naz; Shahid Waseem (Malaria Journal, 2021)
Abstract Background Plasmodium vivax contributes to over 70% malaria burden in Pakistan, but limited data exists on various aspects including genetic diversity of the parasite as compared to other parts of the world. Since the information about the genetic diversity of P. vivax assists to understand the population dynamics of the parasite, the current study was designed to understand population divergence of P. vivax in Pakistan using circumsporozoite protein (pvcsp) and merozoite surface protein-1 (pvmsp-1) genes as molecular markers. Methods The PCR for pvcsp and pvmsp-1 genes was carried out for 150 P. vivax isolates, followed by DNA sequencing of 35 and 30, respectively. Genetic diversity and polymorphism were analysed using ChromasPro, ClustalW, MEGA7, DnaSP v.5 and WebLogo programs. Results The PCR for pvcsp and pvmsp-1 genes was carried out for 150 P. vivax isolates and resulting the PCR products of 1100 bp for pvcsp and ~ 400 bp for pvmsp-1 genes, respectively. In the central-repeat region (CRR) of pvcsp gene, sequences comprised of four variable repeats of PRMs, out of which GDRADGQPA (PRM1), GDRAAGQPA (PRM2) were more extensively dispersed among the P. vivax isolates. Partial sequences (~ 400 bp) of block 2 of pvmsp-1 gene depicted high level of diversity. Conclusion The results revealed the polymorphism and genetic diversity especially at the CRR of pvcsp and block 2 of pvmsp-1 genes, respectively. The base-line data presented here warrants future studies to investigate more into the genetic diversity of P. vivax with large sample size from across the country for better understanding of population dynamics of P. vivax that will help to control malaria at individual and community level.